Theoretical considerations about attachment in adults - Ortiz-Granja, Dorys (2019)
Attachment theory is a significant contribution in the psychological field in order to understand how children build their bonds with a significant person and how this schema affects their development during adolescence and adulthood both in the creation of bonds and in other important aspects, such as learning and social relationships. Possible impacts on cognitive and affective processes are analyzed when the building of secure attachment is disrupted throughout the life cycle but, mainly, during young adulthood. This is due to the significant areas of development during this life stage, such as university, mate searching and work. Therefore, this article reviews theoretical issues of attachment, its relational involvement and its impact on the building of representational patterns that determine the evolution of people and their relationships. Additionally, this study analyzes the types of attachment and describes relevant research with this theory framework, as well as various ways of assessing attachment through scales and other instruments validated in Europe and Asia. It is concluded that there is a weak development of the psychometric area in Latin America; therefore, it is important and necessary to expand this area in the Ecuadorian context. ies.